Electronic cigarettes in Canada: Prevalence of use and perceptions among youth and young adults - Czoli, Christine D. (Can J Public Health, 2014)
OBJECTIVES: The goal of this study was to examine the prevalence and perceptions of electronic cigarette use among Canadian youth and young adults. METHODS: A sample of 1,188 youth and young adults age 16–30 years were recruited from an online panel of Canadians in 2012. After viewing an image of an e-cigarette, respondents answered questions regarding their use and perceptions of e-cigarettes. RESULTS: Close to half of respondents (43.4%) had seen e-cigarettes advertised or for sale. A total of 1 6.1 % reported trying an e-cigarette (5.2% non-smokers, 1 8.9% former smokers, and 34.5% current smokers), and 5.7% reported use in the past 30 days (0.8% non-smokers, 1.4% former smokers, and 15.0% current smokers). Compared to non-smokers, former smokers and current smokers were more likely to have tried e-cigarettes (OR=4.25 and OR=9.84, respectively), and current smokers were more likely to have tried e-cigarettes than former smokers (OR=2.32). Current smokers were also more likely to be current users of e-cigarettes than both former smokers (OR=15.15) and non-smokers (OR=4.43). Smokers were interested in trying e-cigarettes to help them quit smoking (80.4%), as a long-term replacement for cigarettes (77.8%), or to use in places where they cannot smoke (80.9%). CONCLUSIONS: Awareness of e-cigarettes among surveyed youth and young adults is quite high. Almost one fifth (16.1 %) of participants reported trying e-cigarettes, with evidence of use among non-smokers.